2022
DOI: 10.3389/fendo.2022.843912
|View full text |Cite
|
Sign up to set email alerts
|

Undercarboxylated Osteocalcin and Its Associations With Bone Mineral Density, Bone Turnover Markers, and Prevalence of Osteopenia and Osteoporosis in Chinese Population: A Cross-Sectional Study

Abstract: ObjectiveUndercarboxylated osteocalcin (ucOC) is one form of osteocalcin lacking full carboxylation, which plays an important role in bone homeostasis, glucose homeostasis, and energy metabolism. Our aim is to obtain the profile of serum ucOC level according to gender and age and explore its associations with bone mineral density (BMD), bone turnover markers (BTMs), and prevalence of osteopenia and osteoporosis in the Chinese population.MethodsThis is a cross-sectional study with 900 subjects, composed of 431 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In a recent study by Xu et al. ( 31 ), decreased OCN was associated with bone turn markers and osteopenia, and osteoporosis. Thus, decreased OCN in NAFLD patients could be a potential factor leading to osteoporosis.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study by Xu et al. ( 31 ), decreased OCN was associated with bone turn markers and osteopenia, and osteoporosis. Thus, decreased OCN in NAFLD patients could be a potential factor leading to osteoporosis.…”
Section: Discussionmentioning
confidence: 90%
“…The de ciency of 25 hydroxyvitamin D will lead to the decrease of serum calcium, and then lead to osteoporosis [18,19]. P1NP and osteocalcin are indicators re ecting the ability of OCN, and when their levels increase, the body's osteogenic activity is more active [20][21][22][23]. β-CTX is an indicator of the activity of human osteoclasts, and its clinical signi cance is to show the degree of osteoclast absorption of bone.…”
Section: Discussionmentioning
confidence: 99%
“…21,46,47 Although it is not yet known whether the inhibitory action of OCN on the bone matrix mineralization is attributed to its carboxylated or undercarboxylated form, a recent clinical study has shown a correlation between increased serum levels of undercarboxylated OCN and a reduction in bone mineral density, both in men and in women. 48 Therefore, the exact role of OCN during bone matrix mineralization remains controversial. Nevertheless, the results of our study support the idea that carboxylated OCN stimulates bone matrix mineralization, at least during the earliest stages of alveolar process formation in rat maxillae.…”
Section: Discussionmentioning
confidence: 99%